Anti-erosion alumina-calcium oxide refractory material and preparation method thereof

By developing an anti-eroding aluminum aluminum-calcium oxide refractory resistance material including high aluminum alum, South African red pillar stones, and electric melting white ritual jade, it solves the problem of material erosion caused by H2 and CO atmosphere in the hydrogen-based vertical furnace. The high temperature stability and long life of the material improve the benefits of use.

CN119371189APending Publication Date: 2025-01-28ZHENGZHOU ANNEC IND
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411483756.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The H2 and CO atmosphere in the hydrogen-based vertical furnace leads to chemical reduction of the alumina material, which seriously erodes, shortening the service life of the material.

Method used

It uses an anti-eroding aluminum oxide-calcium oxide refractory material. Its formula includes high aluminum alum, South African red pillar stones, electric melting white ritual jade, aluminum aluminum micro powder, calcium oxide, oxide and phenolic resin, through firing and ball milling process The steps improve the resistance of the material and high temperature stability.

Benefits of technology

This refractory material shows good anti -H2, CO erosion and high temperature stability in the hydrogen -based vertical furnace. It is not easy to crack or peel off, extend the service life, and improves economic benefits.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides an anti-erosion aluminum oxide-calcium oxide refractory material and a preparation method thereof. The refractory material comprises the following raw materials in parts by mass: 20-30 parts of high-alumina bauxite particles with the particle size of 4-1mm; 15-20 parts of South African andalusite with a particle size of 1-0 mm; 10-15 parts of fused white corundum particles with the particle size of 0-0.2 mm; 20-25 parts of high-alumina bauxite powder with a particle size of less than 0.088 mm; 10-15 parts of fused white corundum powder with a particle size of less than 0.074 mm; 5-10 parts of alumina micro powder with a particle size of less than 6 [mu] m; 5-10 parts of calcium oxide with a particle size of less than 0.074 mm; 3-5 parts of electric furnace recycled silicon dioxide micro powder with the particle size being lower than 5 microns; 1-2 parts of cerium oxide; and 3-4 parts of phenolic resin. The refractory material has the advantages of higher strength, favorable H2 and CO corrosion resistance, favorable high-temperature stability and no cracking or peeling in the use process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of refractory materials, and more particularly to a refractory material for a hydrogen-based vertical furnace. 2 , CO erosion alumina-calcium oxide refractory materials and their preparation methods. Background Art

[0002] To achieve carbon emission reduction targets, the steel industry needs to innovate traditional smelting processes, and hydrogen metallurgy is an excellent metallurgical technology to achieve low-carbon near-zero emissions. 2 When there is a reducing atmosphere containing carbon oxides, hydrogen, and especially steam at least temporarily at high temperature, the aluminum oxide at the furnace surface is chemically reduced to gaseous aluminum suboxide and / or aluminum hydroxide, which will be corroded during use. In aluminum silicate refractory materials, hydrogen decomposes mullite to form corundum and silicon monoxide. CO reduces and precipitates the oxides of the refractory materials, and the service life of the refractory materials is greatly reduced.

[0003] Therefore, in order to extend the service life of hydrogen-based vertical furnaces, it is necessary to develop an anti-H 2 , refractory materials corroded by CO. Summary of the invention

[0004] In order to solve the deficiencies in the prior art, the present invention provides a corrosion-resistant alumina-calcium oxide refractory material and a preparation method thereof. The refractory material has high strength, good H 2 , CO erosion, good high temperature stability, and will not crack or peel off during use.

[0005] In order to achieve the above object, the specific scheme adopted by the present invention is: A corrosion-resistant alumina-calcium oxide refractory material comprising the following raw materials in parts by mass: 20-30 parts of high-alumina bauxite particles with a particle size of 4-1 mm; 15-20 parts of South African andalusite with a particle size of 1-0 mm; 10-15 parts of fused white corundum particles with a particle size of 0-0.2 mm; 20-25 parts of high alumina powder with a particle size less than 0.088 mm; 10-15 parts of fused white corundum powder with a particle size less than 0.074mm; 5-10 parts of alumina powder with a particle size less than 6 μm; 5-10 parts of calcium oxide with a particle size less than 0.074 mm; 3-5 parts of silica powder recovered from electric furnace with particle size less than 5μm; 1-2 parts of cerium oxide; 3-4 parts of phenolic resin.

[0006] Preferably, the following raw materials are included in parts by weight: 25 parts of high-alumina bauxite particles with a particle size of 4-1 mm; 15 parts of South African andalusite with a particle size of 1-0 mm; 15 parts of fused white corundum particles with a particle size of 0-0.2 mm; 22 parts of high-alumina powder with a particle size of less than 0.088 mm; 10 parts of fused white corundum powder with a particle size less than 0.074 mm; 5 parts of alumina powder with a particle size less than 6 μm; 5 parts of calcium oxide with a particle size less than 0.074 mm; 3 parts of silica powder recovered from electric furnace with particle size less than 5 μm; 1 part of cerium oxide; 4 parts of phenolic resin.

[0007] Furthermore, in the high-alumina bauxite particles or high-alumina bauxite powder, Al 2 O 3 The mass fraction of ≥88%; Al in fused white corundum particles or fused white corundum powder 2 O 3 The mass fraction is ≥99.5%; Al in South African andalusite 2 O 3 The mass fraction of ≥55%; Al in alumina powder 2 O 3 The mass fraction is ≥99.5%; The mass fraction of CaO in calcium oxide is ≥75%; Electric furnace recovery of SiO2 from silica powder 2 The mass fraction is ≥98.5%.

[0008] A method for preparing a corrosion-resistant alumina-calcium oxide refractory material mainly comprises the following steps: Step 1, weigh each raw material according to the above mass fractions; Step 2: Grind calcium oxide and cerium oxide with a particle size of less than 0.074 mm in a ball mill for 12 hours, then place them in a sagger and put them into a kiln for firing at a temperature of 1450-1550°C for 7-9 hours. After leaving the kiln, ball mill them again for 3 hours and then pass them through a 0.074 mm sieve to take the sieve-off material; Step 3: Put high-alumina bauxite particles with a particle size of 4-1mm, South African garnet with a particle size of 1-0mm, and fused white corundum particles with a particle size of 0-0.2mm into a sand mixer, add phenolic resin and mix for 1-2 minutes; Step 4: Place high-alumina bauxite powder with a particle size of less than 0.088 mm, fused white corundum powder with a particle size of less than 0.074 mm, alumina powder with a particle size of less than 6 μm, electric furnace recovered silica powder with a particle size of less than 5 μm, and the sun-dried material obtained in step 2 in a premixer and mix for 1-2 minutes to obtain premixed fine powder; Step 5: Add the premixed fine powder obtained in step 4 to the mixing and grinding equipment in step 3, and wet-grind for 5-7 minutes to obtain corrosion-resistant alumina-calcium oxide refractory material.

[0009] It should be noted that in the process of preparing alumina-calcium oxide refractory materials, calcium oxide and cerium oxide are first fired, and the pre-reaction of calcium oxide and cerium oxide can improve the anti-hydration ability of calcium oxide and improve the service life of refractory materials. Steps 3 and 4 are respectively mixed with coarse materials and fine materials. Pre-mixing the matrix of different particle sizes can make the raw materials fully mixed and uniform, avoid errors and inhomogeneities caused by direct mixing, and shorten the time of subsequent mixing of coarse materials and fine materials. Finally, the premixed fine powder is added to the premixed coarse powder, and wet milling and mixing are performed to obtain the final refractory material.

[0010] The role of each raw material in the present invention is described below. High alumina: strong chemical stability and high temperature resistance, ensuring the high temperature resistance, high strength, good high temperature volume stability, corrosion resistance and durability of the refractory material. South African andalusite: The added andalusite makes the material have the advantages of high temperature resistance, strong thermal shock stability, chemical stability and strong resistance to chemical erosion. The used andalusite gradually mullites under high temperature conditions, and the generated SiO 2 Then it forms secondary mullite with the added alumina powder; the interlaced network structure of columnar and needle-shaped mullite increases the strength of the material, improves the load softening temperature of the material, and makes the material have good thermal shock stability and erosion resistance. Fused white corundum: Fused white corundum has a small thermal expansion coefficient, which can make the thermal expansion of refractory materials smaller and make the stability of refractory materials better. Alumina powder: can improve the secondary mullite of andalusite. Silica powder: reacts with calcium oxide to form calcium silicate, which can improve the strength and high temperature load softening temperature of refractory materials. Cerium oxide: improves the hydration resistance of calcium oxide. After adding cerium oxide, sufficient ion thermal movement makes the contact between aluminum and silicon phases more complete, improves the reaction degree of synthetic mullite phase, and reduces the demand for aluminum and silicon content in raw materials. Among them, cerium oxide can effectively improve the microstructure of the material, promote sintering, reduce pores, and increase density. Phenolic resin: used as a binder.

[0011] Beneficial effects:

[0012] (1) The pores in the refractory material determine the stability of the refractory material against corrosive substances. The present invention selects refractory raw materials with high density and low water absorption rate and adopts multi-level batching. Under the condition of appropriately increasing the firing temperature, a refractory material with low porosity is obtained, which has good H resistance under the special working conditions of the hydrogen-based vertical furnace. 2 , CO gas erosion.

[0013] (2) The present invention uses high-purity calcium oxide, and pre-reacts calcium oxide with cerium oxide before the test begins. The reacted substances and the anti-hydration ability of calcium oxide are improved to increase the service life of the refractory material.

[0014] (3) In the present invention, the silicon powder reacts with calcium oxide to form calcium silicate, which can improve the strength and high temperature load softening temperature of the refractory material.

[0015] (4) The refractory material of the present invention utilizes active alumina powder to enhance the secondary mullite transformation of andalusite, thereby further enhancing the strength of the refractory material and generating a certain volume expansion to offset the shrinkage generated under high temperature strength and enhance its high temperature load softening temperature.

[0016] (5) The present invention adopts a scientific and reasonable particle grading method, optimizes the matrix combination, and adds an appropriate amount of phenolic resin to effectively improve the construction performance of the refractory material.

[0017] (6) The corrosion-resistant alumina-calcium oxide refractory material for hydrogen-based vertical furnaces in the present invention has good resistance to H 2 , CO gas erosion, anti-hydration performance and stable high temperature performance, the hydrogen-based vertical furnace has a longer service life. The refractory material in the present invention can be constructed by applying, with obvious economic benefits, forming a technical advantage for manufacturers, with a higher premium, and a longer service life for the user, diluting the use cost. DETAILED DESCRIPTION

[0018] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0019] In order to more clearly understand the technical content of the present invention, the following examples are given in detail. The Al content of the high-alumina bauxite particles or high-alumina bauxite powder in the raw materials used in the following examples is described in detail. 2 O 3 The mass fraction of Al in fused white corundum particles or fused white corundum powder is ≥88%. 2 O 3The mass fraction of Al in the South African andalusite is ≥99.5%. 2 O 3 Mass fraction ≥ 55%, the Al2O3 powder 2 O 3 The mass fraction is ≥99.5%, the mass fraction of CaO in calcium oxide is ≥75%, the mass fraction of SiO2 in the silicon dioxide powder recovered by the electric furnace is ≥98.5%, and the mass fraction of cerium dioxide in the cerium oxide is ≥99%.

[0020] Example 1

[0021] A corrosion-resistant alumina-calcium oxide refractory material of this embodiment is prepared according to the following steps: Step 1, weigh 25 parts of high-alumina bauxite particles with a particle size of 4-1mm, 15 parts of South African garnet with a particle size of 1-0mm, 15 parts of fused white corundum particles with a particle size of 0-0.2mm, 22 parts of high-alumina bauxite powder with a particle size less than 0.088mm, 10 parts of fused white corundum with a particle size less than 0.074mm, 5 parts of alumina powder with a particle size less than 6μm, 5 parts of calcium oxide with a particle size of 0.075mm, 3 parts of electric furnace recovered silica powder with a particle size less than 5μm, 1 part of cerium oxide, and 4 parts of phenolic resin; Step 2: grind calcium oxide and cerium oxide with a particle size of less than 0.074 mm in a ball mill for 12 hours, then place them in a sagger and put them into a kiln for firing at 1500°C for 8 hours. After leaving the kiln, ball mill them again for 3 hours and then pass them through a 0.074 mm sieve to take the sieve-undersized material; Step 3: Put high-alumina bauxite particles with a particle size of 4-1 mm, South African andalusite with a particle size of 1-0 mm, and fused white corundum particles with a particle size of 0-0.2 mm into a sand mixer, add phenolic resin and mix for 1 minute; Step 4: Place high-alumina bauxite powder with a particle size of less than 0.088 mm, fused white corundum powder with a particle size of less than 0.074 mm, alumina powder with a particle size of less than 6 μm, electric furnace recovered silica powder with a particle size of less than 5 μm, and the sun-dried material obtained in step 2 in a premixer and mix for 1 minute to obtain a premixed fine powder; Step 5: Add the premixed fine powder obtained in step 4 to the mixing and grinding equipment in step 3, and wet-grind for 5 minutes to obtain corrosion-resistant alumina-calcium oxide refractory material.

[0022] Comparative Example 1

[0023] A corrosion-resistant alumina-calcium oxide refractory material of this embodiment is prepared according to the following steps: Step 1, weigh 20 parts of high-alumina bauxite particles with a particle size of 4-1mm, 17 parts of South African garnet with a particle size of 1-0mm, 15 parts of fused white corundum particles with a particle size of 0-0.2mm, 22 parts of high-alumina bauxite powder with a particle size below 0.088mm, 7 parts of fused white corundum with a particle size below 0.074mm, 5 parts of alumina powder with a particle size below 6μm, 8 parts of calcium oxide with a particle size of 0.075mm, 3 parts of electric furnace recovered silica powder with a particle size below 5μm, 1 part of cerium oxide, and 4 parts of phenolic resin; Step 2: grind calcium oxide and cerium oxide with a particle size of less than 0.074 mm in a ball mill for 12 hours, then place them in a sagger and put them into a kiln for firing at 1500°C for 8 hours. After leaving the kiln, ball mill them again for 3 hours and then pass them through a 0.074 mm sieve to take the sieve-undersized material; Step 3: Put high-alumina bauxite particles with a particle size of 4-1mm, South African garnet with a particle size of 1-0mm, and fused white corundum particles with a particle size of 0-0.2mm into a sand mixer, add phenolic resin and mix for 2 minutes; Step 4: Place high-alumina bauxite powder with a particle size of less than 0.088 mm, fused white corundum powder with a particle size of less than 0.074 mm, alumina powder with a particle size of less than 6 μm, electric furnace recovered silica powder with a particle size of less than 5 μm, and the sun-dried material obtained in step 2 in a premixer and mix for 2 minutes to obtain premixed fine powder; Step 5: Add the premixed fine powder obtained in step 4 to the mixing and grinding equipment in step 3, and wet-grind for 7 minutes to obtain corrosion-resistant alumina-calcium oxide refractory material.

[0024] Comparative Example 2

[0025] In this embodiment, an anti-H 2 , CO erosion alumina-calcium oxide refractory is prepared according to the following steps: Step 1, weigh 25 parts of high-alumina bauxite particles with a particle size of 4-1mm, 15 parts of South African garnet with a particle size of 1-0mm, 15 parts of fused white corundum particles with a particle size of 0-0.2mm, 25 parts of high-alumina bauxite powder with a particle size below 0.088mm, 10 parts of fused white corundum with a particle size below 0.074mm, 5 parts of alumina powder with a particle size below 6μm, 5 parts of calcium oxide with a particle size of 0.075mm, 0 parts of electric furnace recovered silica powder with a particle size below 5μm, 1 part of cerium oxide, and 4 parts of phenolic resin; Step 2: grind calcium oxide and cerium oxide with a particle size of less than 0.074 mm in a ball mill for 12 hours, then place them in a sagger and put them into a kiln for firing at 1500°C for 8 hours. After leaving the kiln, ball mill them again for 3 hours and then pass them through a 0.074 mm sieve to take the sieve-undersized material; Step 3: Put high-alumina bauxite particles with a particle size of 4-1 mm, South African andalusite with a particle size of 1-0 mm, and fused white corundum particles with a particle size of 0-0.2 mm into a sand mixer, add phenolic resin and mix for 1 minute; Step 4: Place high-alumina bauxite powder with a particle size of less than 0.088 mm, fused white corundum powder with a particle size of less than 0.074 mm, alumina powder with a particle size of less than 6 μm, electric furnace recovered silica powder with a particle size of less than 5 μm, and the sun-dried material obtained in step 2 in a premixer and mix for 1 minute to obtain a premixed fine powder; Step 5: Add the premixed fine powder obtained in step 4 to the mixing and grinding equipment in step 3, and wet-grind for 5 minutes to obtain corrosion-resistant alumina-calcium oxide refractory material.

[0026] The laboratory test indicators of the refractory materials obtained in Example 1 and Comparative Examples 1-2 are shown in Table 1. Among them, the standards used for the test are: the preparation method of refractory product samples adopts GB / T 7321, the bulk density and true porosity test methods adopt GB / T 2997, the chemical analysis adopts GB / T 6900, the room temperature compressive strength adopts GB / T 5072.1, the heating permanent line change adopts GB / T 5988, and the load softening temperature adopts YB / T 370.

[0027] Table 1 Performance indicators of refractory materials prepared in Example 1 and Comparative Examples 1-2 Example 1 Comparative Example 1 Comparative Example 2 <![CDATA[Chemical composition, (Al 2 O 3 %)]]> 64 61 66 Apparent porosity, % 19.7 21.3 21.5 <![CDATA[Bulk density, g / cm 3 > 2.42 2.39 2.35 Compressive strength at room temperature, MPa 57 55 48 Line change rate after burning 1500×3h, % -0.2~0.2 -0.3~0.3 -0.3~0.3 <![CDATA[Softening temperature under load, °C (0.2 MPa, T 0.6 )]]> 1670 1650 1620 <![CDATA[Compressive strength, MPa, (H 2 erosion for 24 h)]]> 43 35 25 Compressive strength, MPa, (CO erosion 24h) 45 30 27

[0028] As shown in Table 1, compared with Comparative Examples 1-2, the refractory material prepared in Example 1 has better performance. This is mainly because its room temperature compressive strength is higher, the porosity is lower, and the linear change rate is smaller under high temperature conditions, which can ensure the initial use of the refractory material under the special working conditions of the hydrogen-based vertical furnace. At the same time, as time increases in H 2 Its compressive strength decreases less under the erosion of H and CO, and its anti-erosion effect is the best. The process ratio of the present invention shows good resistance to H 2 and CO erosion, it can increase the service life of the furnace in the complex working environment of the hydrogen-based vertical furnace and create good economic benefits.

[0029] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any equivalent changes or modifications made according to the essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A corrosion-resistant alumina-calcium oxide refractory material, characterized in that: Contains the following raw materials in parts by weight: 20-30 parts of high-alumina bauxite particles with a particle size of 4-1 mm; 15-20 parts of South African andalusite with a particle size of 1-0 mm; 10-15 parts of fused white corundum particles with a particle size of 0-0.2 mm; 20-25 parts of high alumina powder with a particle size less than 0.088 mm; 10-15 parts of fused white corundum powder with a particle size less than 0.074mm; 5-10 parts of alumina powder with a particle size less than 6 μm; 5-10 parts of calcium oxide with a particle size less than 0.074 mm; 3-5 parts of silica powder recovered from electric furnace with particle size less than 5μm; 1-2 parts of cerium oxide; 3-4 parts of phenolic resin.

2. The corrosion-resistant alumina-calcium oxide refractory material according to claim 1, characterized in that: Contains the following raw materials in parts by weight: 25 parts of high-alumina bauxite particles with a particle size of 4-1 mm; 15 parts of South African andalusite with a particle size of 1-0 mm; 15 parts of fused white corundum particles with a particle size of 0-0.2 mm; 22 parts of high-alumina powder with a particle size of less than 0.088 mm; 10 parts of fused white corundum powder with a particle size less than 0.074 mm; 5 parts of alumina powder with a particle size less than 6 μm; 5 parts of calcium oxide with a particle size less than 0.074 mm; 3 parts of silica powder recovered from electric furnace with particle size less than 5 μm; 1 part of cerium oxide; 4 parts of phenolic resin.

3. The corrosion-resistant alumina-calcium oxide refractory material according to claim 1, characterized in that: The mass fraction of Al2O3 in high-alumina bauxite particles or high-alumina bauxite powder is ≥88%; The mass fraction of Al2O3 in fused white corundum particles or fused white corundum powder is ≥99.5%; The mass fraction of Al2O3 in South African andalusite is ≥55%; The mass fraction of Al2O3 in alumina powder is ≥99.5%; The mass fraction of CaO in calcium oxide is ≥75%; The mass fraction of SiO2 in the silica powder recovered by electric furnace is ≥98.5%.

4. A method for preparing a corrosion-resistant alumina-calcium oxide refractory material, characterized in that: The main steps include: Step 1, weighing each raw material according to the mass fraction described in claim 1; Step 2: Grind calcium oxide and cerium oxide with a particle size of less than 0.074 mm in a ball mill for 12 hours, then place them in a sagger and put them into a kiln for firing at a temperature of 1450-1550°C for 7-9 hours. After leaving the kiln, ball mill them again for 3 hours and then pass them through a 0.074 mm sieve to take the sieve-off material; Step 3: Put high-alumina bauxite particles with a particle size of 4-1mm, South African garnet with a particle size of 1-0mm, and fused white corundum particles with a particle size of 0-0.2mm into a sand mixer, add phenolic resin and mix for 1-2 minutes; Step 4: Place high-alumina bauxite powder with a particle size of less than 0.088 mm, fused white corundum powder with a particle size of less than 0.074 mm, alumina powder with a particle size of less than 6 μm, electric furnace recovered silica powder with a particle size of less than 5 μm, and the sun-dried material obtained in step 2 in a premixer and mix for 1-2 minutes to obtain premixed fine powder; Step 5: Add the premixed fine powder obtained in step 4 to the mixing and grinding equipment in step 3, and wet-grind for 5-7 minutes to obtain corrosion-resistant alumina-calcium oxide refractory material.

Citation Information

Patent Citations

  • Refractory material used for lance for molten iron pretreatment and application thereof

    CN102276270A

  • Castable with resistance to reducing atmosphere

    CN105967664A

  • Antihydration MgO-CaO clinker and its preparation method

    CN1478754A

  • Oxide ceramics multiple phase refractory material

    CN1919796A

  • Mullite ceramic composition

    JP1989183461A